APLIKASI KLASIFIKASI GENRE MUSIK MENGGUNAKAN METODE NAIVE BAYES BERBASIS DESKTOP - Hendrawaty; Dimas Rama Nugraa; Azhar (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2020)
Voice recognition is a part of sound processing that can be used to recognize music. The use of music based on the genres contained in it has been used in everyday life. However, analyzing the genre of a music on a computer is a difficult thing to do. This study describes the results of the study of the genre classification system on a song. This research is to create a system that can detect the genres contained in the music. Literature study was carried out on each part of the system, then the approach that was considered the best in this design was formulated. This study used the Discreat Transform Fourier method. As a signal processing process, it is useful to find the features of the sound. For the classification process using the Naive Bayes method. Results of all tested genres that are recognizable 66%.